Hemodialysis in neonates and infants: A systematic review. Issue 3 (5th November 2017) - Raina, Rupesh; Vijayaraghavan, Prashanth; Kapur, Gaurav; Sethi, Sidharth Kumar; Krishnappa, Vinod; Kumar, Deepak; Bunchman, Timothy E.; Bolen, Shari D; Chand, Deepa
Abstract: Hemodialysis (HD) in neonates and infants poses unique challenges due to high risks of mortality attributable to obligatory small blood flow volumes. Although HD is often necessary in neonates, its effectiveness and feasibility are poorly understood. The aim of this review is to describe in detail the few studies reporting on HD in neonates and infants (<12 months old) and then dissertate more broadly on the subject with an emphasis on recent innovations with potential to overcome traditional barriers for effective HD in this population. We detail the clinical characteristics, outcomes, technical considerations, maintenance and complications associated with HD, and provide guidance for addressing challenges associated with HD in this population.